2022
DOI: 10.1177/11206721221124673
|View full text |Cite
|
Sign up to set email alerts
|

Impact on corneal morphology after cataract surgery with intracameral moxifloxacin in neglected hard cataracts

Abstract: Aim To evaluate corneal morphology after use of 0.5% intracameral moxifloxacin (ICM) in cataract surgery in patients who presented late with hard cataracts. Methods Cross-sectional study conducted from June-2021 to December-2021 at a tertiary eye-care center. 90 patients over 60 years with high-risk characteristics for Covid-19, who presented late with higher grades of nuclear-sclerosis (NS), were included. They underwent phacoemulsification and 0.5%moxifloxacin (0.1 ml) was injected intracamerally at the end … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…One study showed that preservative-free intracameral 0.5% moxifloxacin/0.1% dexamethasone ophthalmic solution, Vigadexa (Alcon, Inc.), did not lead to increased endothelial cell loss and no patient showed signs of TASS [67 ▪ ]. Other studies, including a prospective randomized trial, showed no increased safety risk, changes in macular thickness, choroidal thickness, or endothelial cell count [34,35,52,68,69,70 ▪ ]. Based on available evidence, we believe moxifloxacin is well tolerated for clinical use at approximately 0.5 mg per 0.1 ml.…”
Section: Adverse Events Associated With Intracameral Moxifloxacinmentioning
confidence: 83%
“…One study showed that preservative-free intracameral 0.5% moxifloxacin/0.1% dexamethasone ophthalmic solution, Vigadexa (Alcon, Inc.), did not lead to increased endothelial cell loss and no patient showed signs of TASS [67 ▪ ]. Other studies, including a prospective randomized trial, showed no increased safety risk, changes in macular thickness, choroidal thickness, or endothelial cell count [34,35,52,68,69,70 ▪ ]. Based on available evidence, we believe moxifloxacin is well tolerated for clinical use at approximately 0.5 mg per 0.1 ml.…”
Section: Adverse Events Associated With Intracameral Moxifloxacinmentioning
confidence: 83%
“…However, limited studies have reported a thicker cornea in diabetics [ 24 - 27 ]. This difference in agreement needs to be reinforced in the presence of biochemical factors, including glycemic controls, which may cause variations in swelling pressure and increased corneal thickness [ 28 ]. It is further pertinent to enforce that different studies have assessed various corneal parameters using different contact and non-contact equipment, which use automatic, semi-automatic, or manual methods.…”
Section: Discussionmentioning
confidence: 99%